(untitled) (Archaeologia Adriatica, 2017)
Bibliography of professor Zdenko Brusić reveals a rich life of a curator, museum counselor, director of the Archaeological Museum in Zadar, and first and foremost a scholar and person who will be remembered as one of the founders of underwater archaeology. Rich and diverse professional life of professor Brusić resulted in 127 bibliographic units dealing with different themes.